PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN FASILITAS KERJA TERHADAP KEPUASAN KERJA PADA BADAN PENGELOLAAN KEUANGAN PENDAPATAN DAERAH KOTA BINJAI: PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN FASILITAS KERJA TERHADAP KEPUASAN KERJA PADA BADAN PENGELOLAAN KEUANGAN PENDAPATAN DAERAH KOTA BINJAI - Devi, Aurea Suspitta; Rizky, Muhammad Chaerul (Jurnal Ilmu Manajemen (JIMMU), 2024)
Human resources remain a focus and mainstay for companies to survive in the era of globalization. Human resources play a crucial role in every company activity. Even if supported by excessive facilities and resources, without the support of reliable human resources, company activities will not be completed properly. This shows that human resources are one of the key elements that must be considered with all their needs. Research Objective: To determine whether leadership, organizational culture, and work facilities simultaneously have a positive and significant effect on job satisfaction of employees at the Regional Revenue Finance Agency of Binjai City. Based on the level of explanation, this research is associative research. Associative or causal research (cause and effect relationships). The research results on leadership with a regression coefficient of 0.476, followed by a t-value of 4.771 with a t-table value of 1.9906. Organizational Culture with a regression coefficient of 0.838, followed by a t-value of 8.551 with a t-table value of 1.9906. The work facilities variable with a regression coefficient of 0.491, followed by a t-value of 4.189 with a t-table value of 1.9906, and the F-test result simultaneously obtained an F-value of 25.586 with a significance level of 0.000. While the F-table value is 2.72. The F-value > F-table (25.586 > 2.72) and the significance level (0.000 < 0.05) means that leadership, organizational culture, and work facilities have a positive and significant effect on the dependent variable of job satisfaction of employees at the Regional Revenue Finance Agency of Binjai City. Conclusion: leadership, organizational culture, and work facilities have a significant and positive effect on job satisfaction of employees at the Regional Revenue Finance Agency of Binjai City. Keywords: Leadership, Organizational Culture, Work Facilities, Satisfaction